E-module as an emergency-innovated learning source during the Covid-19 outbreak - Niken Purnamasari; Siswanto Siswanto; Shazia Malik (Psychology, Evaluation, and Technology in Educational Research, 2020)
The COVID-19 pandemic has hugely changed various human activities. This "silent-killer" pandemic attacks almost every single aspect of life in this entire world. In this case, the writer will focus on the education sector as one of the most damaged fields by the pandemic. Every single of its elements has to be quickly adapted to the situation caused by the COVID-19 attack. Stakeholders are continuing hard to formulate the adaptation that can be taken quickly as the most effective way among the uncertain situation. Shortly, regarding the physical distancing campaigned by the most governments, online learning is then considered as the most possible way to keep the learning process going with all its strengths and weaknesses. In accordance with the background of the situation, the writer through this study purposed to determine the effectiveness of e-modules as the emergency innovative learning sources in the middle of this COVID-19 outbreak. Online learning is claimed as an effective solution to keep learning to avoid mass gathering that possibly causes the virus to spread at schools. E-modules belong to interactive teaching sources that are capable to facilitate student to learn independently. They still have chances to learn with interesting, practical, and online-accessible to pursue the learning outcomes as good as possible in term of the emergency self-learning process. To find out the improvement in students learning outcomes after using the e-module through the online learning process, the data analysis in this study was conducted using a paired sample t-test. At last, the results showed that student learning outcomes could be maintained and even improved after the use of the e-module as an emergency innovative learning source during the COVID-19 outbreak.